PERAN ORANGTUA DALAM MENGEMBANGKAN PRESTASI ANAK TUNARUNGU DI SLB CENDANA KECAMATAN MANDAU KABUPATEN BENGKALIS - Rindi, Fajri Septia; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted in Duri, Mandau District, Bengkalis Regency. The objectives of this study were (1) Want to know how parents develop the achievements of children with hearing impairment. (2) Want to know how parents choose the interests and talents of high-achieving deaf children. The method used in this research is descriptive qualitative research method. In accordance with the objectives of this study, namely to determine the role of teachers and parents in developing the interests and talents of deaf children in SLB Cendana, Mandau District, Bengkalis Regency. The qualitative method seeks to understand, describe and interpret the meaning of an event of human behavior interaction. The subjects of this study were determined by purposive sampling technique. This purposive sampling technique is also called judgmental sampling, which is sampling based on research judgment (judgment) of anyone who deserves (meets the requirements) to be sampled and data collection techniques use observation, interviews and documentation of the results of the research. that we can know that the role of parents to deaf children is to guide their children accordingly because if they are after school, of course the parents will trust the school to further develop their achievements. Then the achievements can not be separated from the guidance of parents and teachers in schools who help to continue to hone the abilities of children with hearing impairment. At school children are taught a series of tars to take a series of tests to children with hearing impairment so they can participate in competitions.Keywords: Role of Parents, Achievement, Deaf Children